EMI Technique for Monitoring the Damage Evolution of Initial Damaged Tunnel Invert Concrete Subjected to High Traffic Cyclic Loading. (29th October 2020) - Ye, Yichao; Peng, Limin; Lin, Yuexiang; Liu, Jianwen; Lei, Mingfeng; Fei, Ruizhen
Abstract : The electromechanical impedance (EMI) technique based on the PZT transducer, in the past twenty years of research progress, has demonstrated its potential for cost-effective and high damage-sensitive structural health monitoring. This paper presents an application of EMI technique for damage evolution investigation of initial damaged tunnel invert concrete under high traffic cyclic loading. In the tests, six different levels of initial damage inside the specimens, as the influencing factor, were firstly created by applying a certain number of impacts with a free-falling iron ball. Then, these specimens were applied typical mechanical boundaries similar to that of tunnel invert concrete by an installation specially designed. Finally, the traffic cyclic loading carefully determined was exerted by the MTS815 hydraulic zero-control testing system, to investigate the evolution characteristic of piezoelectric signature of the PZT sensor. The experimental result shows that the conductance signature follows a consistent rightward shifting with the number of cycles increasing, and the larger the initial damage of the specimen, the more obvious the rightward shifting. It indicates that, in general, the traffic cyclic loading is not large enough to make the microcracks propagate to fatigue failure in tunnel invert concrete even if there is a large initial damage. On the contrary, with special mechanical boundaries, the local nominal stiffness of tunnel invert concrete will gradually increase. This phenomenon may be interpreted as an effect of generalized damage recovery. A new damage index, with values between 0 and 1, was then defined to quantify the damage level for quantitative analysis. It was found that the damage recovery behaviors for different initial damaged specimens can be well and uniformly described by an empirical expression, which may be helpful for the damage assessment of tunnel invert concrete under high traffic cyclic loading in the future.